The Vigilante Violence Against Criminality Offenders - Riky Novarizal; Henky Fernando; Rahmat Amin Siregar; Dean Rizky Saputra; Tasya Sofiatul Afrida Nasution; Yuniar Galuh Larasati (Indonesian Journal of Criminal Law, 2025)
This article critically examines the phenomenon of community vigilantism against criminals because these actions are often legitimised by dominant cultural knowledge and meanings. However, this phenomenon tends to be absent from the literature. In addition to responding to the gaps in previous studies, this research also aims to explain the characteristics, factors, and implications of community vigilantism against criminals. This research is based on descriptive qualitative research using a case study approach. The important findings of this study show that the vigilante violence perpetrated by the community against criminals appears in the form of physical and psychological violence, as well as acts of property destruction. These acts are not only influenced by factors such as mass hysteria, disregard for moral standards, and low social cohesion but also have long implications for counterproductive social conditions. This study contributes significantly to evaluating the normalisation of vigilante violence acts against criminals in public spaces while proposing strategies to prevent the adverse effects of vigilante violence acts on social harmony.